International medical technology diffusion - Papageorgiou, Chris; Zachariadis, Marios; Savvides, Andreas (My University, 2007)
Does medical technology generated in frontier countries have a significant impact on health outcomes in the rest of the world? This paper considers a framework where non-frontier countries may benefit from medical innovation that is embodied in medical imports or diffuses in the form of ideas. Using a novel dataset from a cross-section of 63 technology-importing countries, we show that medical technology diffusion is an important contributor to improved health status, as measured by life expectancy and mortality rates.
Keywords: International technology diffusion; Life expectancy; Medical imports; Medical students